2023
DOI: 10.3390/cli11090176
|View full text |Cite
|
Sign up to set email alerts
|

Projections of Changes in Atmospheric Conditions Leading to Storm Surges along the Coast of Santos, Brazil

Marcely Sondermann,
Sin Chan Chou,
Priscila Tavares
et al.

Abstract: This study aims to assess the changes in the atmospheric conditions favorable to storm surges over the Santos Coast in Southeast Brazil. Storm surges can favor high sea level rises and coastal erosion, affecting people and strategic structures in coastal areas. The assessment of the atmospheric conditions was based on the downscaling of climate simulations of the Brazilian Earth System Model by the Eta regional climate model at higher spatial resolution. The detection scheme used by the model was able to repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Future changes in the frequency and intensity of these storm surges will raise the risk of disasters. According to Sondermann et al [6], based on the Eta regional model's downscaling of the Brazilian Earth System Model's (BESM's) [7] projections for RCP4.5 and RCP8.5 greenhouse gas scenarios, the storm surge events characterized by pattern 1 are expected to become more intense. However, these events will continue to be the least frequent in the future.…”
Section: Of 19mentioning
confidence: 99%
“…Future changes in the frequency and intensity of these storm surges will raise the risk of disasters. According to Sondermann et al [6], based on the Eta regional model's downscaling of the Brazilian Earth System Model's (BESM's) [7] projections for RCP4.5 and RCP8.5 greenhouse gas scenarios, the storm surge events characterized by pattern 1 are expected to become more intense. However, these events will continue to be the least frequent in the future.…”
Section: Of 19mentioning
confidence: 99%
“…For example, Quaill et al, (2019) observed the experiences of people with physical disabilities before, during and after a cyclone in Australia to provide input into implementing the Disability Inclusive Disaster Risk Reduction (DiDRR) policy. In addition, Bell et al (2022) investigated the economy-wide repercussions of the biophysical damage due to Cyclone Debbie in Australia using multi-region economic input-output (MRIO) analysis to determine the storm's impact on supply chains (Sondermann et al, 2023). However, Bell et al (2022) determines TC-wind speed ARIs from a series of tropical cyclone datasets to predict the likelihood of extreme winds.…”
Section: Introductionmentioning
confidence: 99%